An Updated View of the Intracellular Mechanisms Regulating Cross-Presentation - Blander, Julie Magarian; Nair-Gupta, Priyanka (Frontiers in Immunology, 2013)
Cross-presentation involves the presentation of peptides derived from internalized cargo on major histocompatibility complex class I molecules by dendritic cells, a process critical for tolerance and immunity. Detailed studies of the pathways mediating cross-presentation have revealed that this process takes place in a specialized subcellular compartment with a unique set of proteins. In this review, we focus on the recently appreciated role for intracellular vesicular traffic, which serves to equip compartments such as endosomes and phagosomes with the necessary apparatus for conducting the various steps of cross-presentation. We also consider how these pathways may integrate with inflammatory signals particularly from pattern recognition receptors that detect the presence of microbial components during infection. We discuss the consequences of such signals on initiating cross-presentation to stimulate adaptive CD8 T cell responses.